Fixed Point Theorems for Nonexpansive Mappings under Binary Relations - Aftab Alam; Reny George; Mohammad Imdad; Md Hasanuzzaman (Mathematics, 2021)
In the present article, we establish relation-theoretic fixed point theorems in a Banach space, satisfying the Opial condition, using the <semantics>R</semantics>-Krasnoselskii sequence. We observe that graphical versions (Fixed Point Theory Appl. 2015:49 (2015) 6 pp.) and order-theoretic versions (Fixed Point Theory Appl. 2015:110 (2015) 7 pp.) of such results can be extended to a transitive binary relation.